2022
DOI: 10.1002/mc.23460
|View full text |Cite
|
Sign up to set email alerts
|

CCT4 knockdown enhances the sensitivity of cisplatin by inhibiting glycolysis in human esophageal squamous cell carcinomas

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common human malignancy characterized by late-stage diagnosis, metastasis, and poor prognosis. Cisplatin (DDP)-based chemotherapy has been the most predominant treatment for patients with ESCC. However, the high rate of DDP resistance and toxicity seriously hinder its clinical application. Then, the optimized strategy and mechanisms for ESCC to enhance DDP sensitivity are in great demand. Accumulating evidence have shown that chaperone proteins are closely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To further analyse the role of dysregulated RTKs on chemoresistance under simulated conditions of limited oxygen (1%), we initially considered the selection of OSCC cell lines that had the greatest resistance to DDP. Recent findings have indicated that KYSE150 cells have the lowest drug sensitivity to DDP [ 21 ]. We thus examined the IC 50 of DDP in different cell lines under low-oxygen conditions and found that this was indeed the case (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further analyse the role of dysregulated RTKs on chemoresistance under simulated conditions of limited oxygen (1%), we initially considered the selection of OSCC cell lines that had the greatest resistance to DDP. Recent findings have indicated that KYSE150 cells have the lowest drug sensitivity to DDP [ 21 ]. We thus examined the IC 50 of DDP in different cell lines under low-oxygen conditions and found that this was indeed the case (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When tumor volume reached about 100 mm 3 , the mice were randomly divided into four groups: CON group, DCA group, DDP group, and DCA + DDP group (5 mice/group). Tumor volume was measured every 3 days, and tumor growth curve was calculated using the formula “length×width 2 × 3.14/6.” The mice were euthanized when the experiment was terminated, and the tumors were collected for further investigation 27 …”
Section: Methodsmentioning
confidence: 99%
“…The mice were euthanized when the experiment was terminated, and the tumors were collected for further investigation. 27…”
Section: In Vivo Tumor Inoculation Mouse Modelmentioning
confidence: 99%
“…75,111,112 Finally, they modulate signalling pathways to promote tumour occurrence and development. 82,113,114 Here, we describe these functions as they relate to the hallmarks of cancer.…”
Section: Cct Subunits In Cancersmentioning
confidence: 99%
“…Second, they regulate the assembly and disassembly of TRiC/CCT and influence its protein folding activity 75,111,112 . Finally, they modulate signalling pathways to promote tumour occurrence and development 82,113,114 . Here, we describe these functions as they relate to the hallmarks of cancer.…”
Section: Cct Subunits In Cancersmentioning
confidence: 99%